Factors associated with the functional performance of older adults with type 2 Diabetes Mellitus (Research, Society and Development, 2020)
The aim of this study was to investigated factors associated with the functional impairment of older adult patients with type 2 diabetes mellitus (type 2 DM) and identify the influence of sociodemographic, clinical, and functional factors in this population. This is an observational analytical, and cross-sectional study, which evaluated 159 individuals of both genders, aged 60 years or older. The WHODAS (World Health Organization Disability Assessment Schedule) total score was analyzed in relation to other variables of the study, using the following statistical tests: Mann-Whitney, Kruskal-Wallis, Dunn’s post hoc, Spearman correlation, and simple linear regression analysis. Significance level was set at 5% (p